Penerapan Metode Bernyanyi dalam Meningkatkan Keterampilan Membaca Permulaan Siswa Sekolah Dasar - Huljannah Arianto, Mifta; Sabani, Fatmaridah; Rahmadani, Ervi; Sukmawaty, Sukmawaty; Guntur, Muhammad; Irfandi, Irfandi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research discusses the implementation of the singing method in enhancing the reading skills of first-grade students at SDN 30 Mattirowalie, Palopo City. The main objective of this study is to describe the implementation of the singing method in early reading instruction and to evaluate its impact on students' reading abilities. This research adopts a classroom action approach, combining qualitative and quantitative descriptive methods in data collection and analysis. Data were collected through observation, interviews, documentation, and tests conducted throughout the research cycle. The research process is divided into four main stages: planning, implementation, observation, and reflection. The researcher acts as a teacher, implementing the singing method in instruction, while the homeroom teacher serves as an observer to collect observational data. The implementation of the singing method proves to be effective, evidenced by increased student enthusiasm in the teaching and learning process and significant improvement in average test scores conducted at the end of each learning cycle. The results consistently improve students' early reading skills from cycle to cycle. The average score in cycle I was 38.2, increased to 57.6 in cycle II, and finally reached its peak in cycle III with an average score of 78.6. This improvement exceeds the Minimum Mastery Criteria (KKM) set by the school at 70, leading to the termination of the research in cycle III as the target has been successfully achieved.